Iron Pathways and Iron Chelation Approaches in Viral, Microbial, and Fungal Infections - Ravneet Chhabra; Aishwarya Saha; Ashkon Chamani; Nicole Schneider; Riya Shah; Meera Nanjundan (MDPI AG, 2020)
Iron is an essential element required to support the health of organisms. This element is critical for regulating the activities of cellular enzymes including those involved in cellular metabolism and DNA replication. Mechanisms that underlie the tight control of iron levels are crucial in mediating the interaction between microorganisms and their host and hence, the spread of infection. Microorganisms including viruses, bacteria, and fungi have differing iron acquisition/utilization mechanisms to support their ability to acquire/use iron (e.g., from free iron and heme). These pathways of iron uptake are associated with promoting their growth and virulence and consequently, their pathogenicity. Thus, controlling microorganismal survival by limiting iron availability may prove feasible through the use of agents targeting their iron uptake pathways and/or use of iron chelators as a means to hinder development of infections. This review will serve to assimilate findings regarding iron and the pathogenicity of specific microorganisms, and furthermore, find whether treating infections mediated by such organisms via iron chelation approaches may have potential clinical benefit.